Drug discovery with an RBM20 dependent titin splice reporter identifies cardenolides as lead structures to improve cardiac filling - Liss, Martin (PLoS One, 2018)
Diastolic dysfunction is increasingly prevalent in our ageing society and an important contributor to heart failure. The giant protein titin could serve as a therapeutic target, as its elastic properties are a main determinant of cardiac filling in diastole. This study aimed to develop a high throughput pharmacological screen to identify small molecules that affect titin isoform expression through differential inclusion of exons encoding the elastic PEVK domains. We used a dual luciferase splice reporter assay that builds on the titin splice factor RBM20 to screen ~34,000 small molecules and identified several compounds that inhibit the exclusion of PEVK exons. These compounds belong to the class of cardenolides and affect RBM20 dependent titin exon exclusion but did not affect RBFOX1 mediated splicing of FMNL3. We provide evidence that cardenolides do not bind to the RNA interacting domain of RBM20, but reduce RBM20 protein levels and alter transcription of select splicing factors that interact with RBM20. Cardenolides affect titin isoform expression. Understanding their mode of action and harnessing the splice effects through chemical modifications that suppress the effects on ion homeostasis and more selectively affect cardiac splicing has the potential to improve cardiac filling and thus help patients with diastolic heart failure, for which currently no targeted therapy exists.